THEORY AND PRACTICE OF INDIVIDUAL SNOW AVALANCHE RISK ASSESSMENT IN THE RUSSIAN ARCTIC - Aleksandr Shnyparkov; Sven Fuchs; Sergey Sokratov; Peter Koltermann; Yury Seliverstov; Marina Vikulina (Geography, Environment, Sustainability, 2012)
In recent years, the Government of the Russian Federation considerably increased attention to the exploitation of the Russian Arctic territories. Simultaneously, the evaluation of snow avalanches danger was enhanced with the aim to decrease fatalities and reduce economic losses. However, it turned out that solely reporting the degree of avalanche danger is not sufficient. Instead, quantitative information on probabilistic parameters of natural hazards, the characteristics of their effects on the environment and possibly resulting losses is increasingly needed. Such information allows for the estimation of risk, including risk related to snow avalanches. Here, snow avalanche risk is quantified for the Khibiny Mountains, one of the most industrialized parts of the Russian Arctic: Major parts of the territory have an acceptable degree of individual snow avalanche risk (<1×10-6). The territories with an admissible (10-4–10-6) or unacceptable (>1×10-4) degree of individual snow avalanche risk (0.5 and 2% of the total area) correspond to the Southeast of the Khibiny Mountains where settlements and mining industries are situated. Moreover, due to an increase in winter tourism, some traffic infrastructure is located in valleys with an admissible or unacceptable degree of individual snow avalanches risk.